Pengaruh Kompensasi Terhadap Kepuasan Kerja dan Implikasinya Terhadap Kinerja Individu Perawat Pada Beberapa Rumah Sakit Swasta di Kota Medan - Aprinawati Aprinawati; Fauziah Agustini; Hilma Harmen (-)
The long-term objective of this study is to contribute to the management of private hospitals in the city of Medan in order to encourage the improvement of individual nurse performance so as to produce excellent service to patients through job satisfaction as an emotional aspect felt by nurses based on the compensation they receive from the hospital. The specific targets to be achieved are to determine the effect of compensation on satisfaction and to determine the effect of job satisfaction on performance and to determine the effect of job satisfaction on the performance of individual nurses at several private hospitals in the city of Medan. The methods that will be used by this research are interviews, questionnaires, and documentation. The method of analysis used is the regression equation model.